Simulated Firefighting Task Performance and Physiology Under Very Hot Conditions - Larsen, Brianna; Snow, Rod; Williams-Bell, Michael; Aisbett, Brad (Frontiers in Physiology, 2015)
Purpose: To assess the impact of very hot (45°C) conditions on the performance of, and physiological responses to, a simulated firefighting manual-handling task compared to the same work in a temperate environment (18°C). Methods: 10 male volunteer firefighters performed a 3-hour protocol in both 18°C (CON) and 45°C (VH). Participants intermittently performed 12 × 1-minute bouts of raking, 6 × 8-minute bouts of low-intensity stepping, and 6 × 20-minute rest periods. The area cleared during the raking task determined work performance. Core temperature, skin temperature, and heart rate were measured continuously. Participants also periodically rated their perceived exertion (RPE) and thermal sensation. Firefighters consumed water ad libitum. Urine specific gravity and changes in body mass determined hydration status. Results: Firefighters raked 19% less debris during the VH condition. Core and skin temperature were 0.99 ± 0.20°C and 5.45 ± 0.53°C higher, respectively, during the VH trial, and heart rate was 14-36 beats.min-1 higher in the VH trial. Firefighters consumed 2950 ± 1034 mL of water in the VH condition, compared to 1290 ± 525 in the CON trial. Sweat losses were higher in the VH (1886 ± 474 mL) compared to the CON trial (462 ± 392 mL), though both groups were hydrated upon protocol completion (USG < 1.020). Participants’ average RPE was higher in the VH (15.6 ± 0.9) compared to the CON trial (12.6 ± 0.9). Similarly, the firefighers' thermal sensation scores were significantly higher in the VH (6.4 ± 0.5) compared to the CON trial (4.4 ± 0.4). Conclusions: Despite the decreased work output and aggressive fluid replacement observed in the VH trial, firefighters’ experienced increases in thermal stress and exertion. Fire agencies should prioritise the health and safety of fire personnel in very hot temperatures, and consider the impact of reduced productivity on fire suppression efforts.